2020
DOI: 10.1101/2020.05.15.098616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV2 (COVID-19) Structural/Evolution Dynamicome: Insights into functional evolution and human genomics

Abstract: The SARS-CoV-2 pandemic, starting in 2019, has challenged the speed at which labs perform science, ranging from discoveries of the viral composition to handling health outcomes in humans. The small ~30kb single-stranded RNA genome of Coronaviruses makes them adept at cross species spread and drift, increasing their probability to cause pandemics. However, this small genome also allows for a robust understanding of all proteins coded by the virus. We employed protein modeling, molecular dynamic simulations, evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Our findings do not support the existence of common coding pathogenic variants for TMPRSS2 among different populations. Accordingly, recent studies identified only a few pathogenic, ultra-rare variants in this gene (Gupta et al, 2020 ; Paniri et al, 2020 ; Sajuthi et al, 2020 ). Therefore, given their rarity, we do not believe that coding variants, except for some rare cases, can determine the diverse susceptibility to viral infection and diverse clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings do not support the existence of common coding pathogenic variants for TMPRSS2 among different populations. Accordingly, recent studies identified only a few pathogenic, ultra-rare variants in this gene (Gupta et al, 2020 ; Paniri et al, 2020 ; Sajuthi et al, 2020 ). Therefore, given their rarity, we do not believe that coding variants, except for some rare cases, can determine the diverse susceptibility to viral infection and diverse clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…All of them exhibit very low AFs ( Figure 1A ). Accordingly, a recent study identified a few functional ultra-rare variants in TMPRSS2 , all of them with AFs < 0.001 (Gupta et al, 2020 ). These findings agree with the recommended benign frequency cut-off of 0.0001 for the TMPRSS2 gene, as from the Varsome database.…”
Section: Analysis Of Genetic Variants Of Tmprss2 Lmentioning
confidence: 99%
“…This study of mutations in the SARS-CoV2 genomes of 128 COVID-19 affected Indian patients has been carried out. Various mutations over the proteins of SARS-CoV2 genomes are presented in the articles [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. A comprehensive list of patients with other associated details are presented in the Table 1 .…”
Section: The Studymentioning
confidence: 99%
“…After constructing the 3D interactome between SARS-CoV-2 and human, we first looked for evidence of interface-specific variation by mapping both gnomAD 58 reported human population variants (Supplemental Table 3) and sequence divergences between SARS-CoV and SARS-CoV-2 (Supplemental Table 4) onto the predicted interfaces. In general, conserved residues have been shown to cluster at protein-protein interfaces 63 , and a recent analysis of SARS-CoV-2 structure and evolution likewise concluded that highly conserved surface residues were likely to drive protein-protein interactions 64 . Consistent with these prior findings at an interactome-wide level, we observed significant depletion for both viral and human variation along the predicted interfaces comparable to that observed on solved human-human interfaces (Fig 2.a).…”
Section: Perturbation Of Human Proteins By Disease Mutations and Bindmentioning
confidence: 99%